Public Street Lighting Monitoring System Uses Telegram-Based Application Wireless Sensor Network - Ilham Muhyidin Nabil; Adnan Rafi Al Tahtawi; Supriyanto (Fakultas Teknik Universitas Pancasila, 2024)
Public Street Lighting (PJU) usually operates all night until early morning without a remote device to adjust the conditions. In monitoring the PJU lights, the officers are still carrying out their duties manually by visiting the place. This study aims to build a PJU monitoring system tool by utilizing the NodeMCU ESP32 as a microcontroller and a wifi module, which will later send notifications via the Telegram Bot. This system uses the ACS712 current sensor to detect the value of the current flowing in public street lighting installations, the VDC voltage sensor to detect the voltage value, and the LDR sensor to detect light. The read data will be processed by ESP32, which will then be sent to the Telegram Bot. The result of this study is a PJU monitoring tool. With this tool, officers can remotely monitor the PJU lights' condition. The Telegram bot will send notification messages to officers at 07.00 and 19.00. In addition, officers can ask about the state of the lights by instructing